Attraction of foreign investments: motivation process - Gutkevych, Svitlana; Zanozovska, Oksana (My University, 2018)
Problems of foreign investments are important issues that are discussed in the world economy and require a practical solution. This is due to the existing trends of globalization and internationalization in the modern economy conditions. International trade and foreign direct investment play an important role in the development of the economies of the states in modern conditions.
Keywords: foreign investment; economy; attractiveness; motivation; policy; іноземні інвестиції; економіка; інвестиційна привабливість; політика; мотивація; процес; іноземний інвестор; кафедра міжнародної економіки